2018
DOI: 10.1002/anie.201810222
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Campylobacter jejuni 81176 Strain Capsular Polysaccharide Repeating Unit Reveals the Absolute Configuration of its O‐Methyl Phosphoramidate Motif

Abstract: The O‐methyl phosphoramidate (MeOPN) motif is a non‐stoichiometric modification of capsular polysaccharides (CPS) in ≈70 % of all Campylobacter jejuni strains. Infections by C. jejuni lead to food‐borne illnesses and the CPS they produce are key virulence factors. The MeOPN phosphorus atom in these CPS is stereogenic and is found as a single stereoisomer. However, to date, the absolute stereochemistry at this atom has been undefined. We report the synthesis of the three repeating units found in C. jejuni 81‐17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
28
0
1
Order By: Relevance
“…As expected, homopolymeric tracts allow a rapid on/off switching of the C. jejuni CPS genes resulting in variations in CPS arrangements even in C. jejuni isolates that have identical gene contents. In addition to the phase variation observed in CPS sugar composition, C. jejuni CPS is also modified with ethanolamine, glycerol, and nonstoichiometric MeOPN modifications in approximately 75% of C. jejuni strains (Thota et al, 2018).…”
Section: Jejuni Capsular Polysaccharide (Cps)mentioning
confidence: 99%
“…As expected, homopolymeric tracts allow a rapid on/off switching of the C. jejuni CPS genes resulting in variations in CPS arrangements even in C. jejuni isolates that have identical gene contents. In addition to the phase variation observed in CPS sugar composition, C. jejuni CPS is also modified with ethanolamine, glycerol, and nonstoichiometric MeOPN modifications in approximately 75% of C. jejuni strains (Thota et al, 2018).…”
Section: Jejuni Capsular Polysaccharide (Cps)mentioning
confidence: 99%
“…The metabolic fate of 234 in the biosynthesis of MeOPN has also been determined. The reactions catalyzed by Cj1415, Cj1416, and Cj1417 ultimately convert 234 to 3′-phospho-5′-cytidine-diphosphoramidate ( 235 ). , The timing of methylation and phosphoryl transfer reactions to ultimately transfer MeOPN to the CPS remain to be delineated, although synthetic routes have demonstrated that the phosphorus in MeOPN exhibits an R -configuration …”
Section: Glutamine-derivedmentioning
confidence: 99%
“…The most unusual of the chemical modifications of the CPS is the incorporation of the unique O -methyl phosphoramidate modification on specific sugar residues (2-acetamido-2-deoxy-β- d -galactofuranose— 17 , d -glycero-α- l -gluco-heptopyranose— 18 ) which so far have only been identified in Campylobacter sp. [43,44,45]. The biosynthetic pathway leading to the formation of the P–N bond in CPS was only recently discovered [46,47,48,49].…”
Section: Natural Products Containing a P–n Bond (Phosphoramidates)mentioning
confidence: 99%